An Analysis Of The Role Of The Social Affairs Office Of Bengkulu City In The Rehabilitation Of Street Children In Bengkulu City - Tito Romadon Saputra; Harius Eko Saputra; Yanuar Rikardo (Utami Publisher, 2026)
City in the rehabilitation of street children in Bengkulu City. The research employed a descriptive qualitative approach. The informants consisted of six individuals, including key informants and main informants. Data were collected through observation, interviews, and documentation. The analysis was based on Edy Suhardono’s role theory (2018), which includes five indicators: action, prescription, evaluation, description, and sanctions. The findings indicate that the role of the Social Affairs Office of Bengkulu City in rehabilitating street children has been adequately implemented. This is reflected in rehabilitation programs such as socialization, outreach activities, shelter services, guidance, and collaboration with relevant institutions. The guidelines applied are based on Bengkulu City Regional Regulation Number 7 of 2017. Program evaluation is conducted through community satisfaction surveys, field observations, and direct assessments. The description shows that most street children come from problematic family backgrounds, poverty, and school dropouts. Sanctions against child exploitation are implemented through preventive, rehabilitative, and repressive measures. Nevertheless, improvements in service quality and more participatory approaches are still needed to enhance the effectiveness of street children rehabilitation programs.